Mechanisms of MoS2 dry film lubricant behavior at low temperatures - Abrar Faiyad; Fakhrul H. Bhuiyan; Azhar Vellore; Duval A. Johnson; Andrew Kennett; Ashlie Martini (Friction)
MoS2 dry film lubricants (DFLs) are widely used in space applications, but their performance can deteriorate at cold temperatures. In this study, reactive molecular dynamics simulations were used to test the hypothesis that this deterioration is attributable to the effect of temperature on the size of MoS2 wear debris generated during sliding. First, tribometer measurements of wear life confirmed the poor tribological performance of MoS2-based DFLs below room temperature. Then, simulations of the temperature-dependent fracture strength of MoS2 provided a mechanism by which smaller flake-like debris may be formed by DFLs at low temperatures. Simulations of MoS2 flakes of varying sizes showed that smaller flakes were more susceptible to water adsorption. However, even in the absence of water, simulations demonstrated that smaller flakes were less lubricious. Analysis of the flake orientation with respect to the shear direction revealed that smaller flakes were less aligned with shear during sliding. This misorientation along with the accelerated adsorption of water by the smaller flakes may contribute to deterioration of the tribological performance at cold temperatures.